Effects of copper-oxide nanoparticles, dissolved copper and ultraviolet radiation on copper bioaccumulation, photosynthesis and oxidative stress in the aquatic macrophyte Elodea nuttallii. (June 2015) - Regier, Nicole; Cosio, Claudia; von Moos, Nadia; Slaveykova, Vera I.
Highlights: UV radiation enhanced Cu uptake from dissolved Cu(II) and CuO NPs by E. nuttallii. UV radiation strongly reduced the photosynthetic capacity of E. nuttallii. Cu(II) inhibited the expression of the COPT1 transporter faster than CuO NPs. UV radiation increased the stress response to Cu(II) and CuO NPs. Abstract: In this study, the uptake and sub-toxic effects of CuO nanoparticles (CuO-NPs), dissolved Cu(II) alone or in combination with UV radiation on the aquatic macrophyte Elodea nuttallii were studied. Emphasis was on Cu accumulation, growth, photosynthesis and the oxidative stress related enzymes peroxidase (POD) and superoxide dismutase (SOD). The results showed stronger Cu accumulation in plants exposed to 10 mg L −1 CuO-NPs, corresponding to 1.4–2 mg L −1 dissolved Cu(II), than to 256 μg L −1 Cu(II). However, the ratio between the accumulated Cu and dissolved Cu in CuO treatments was lower than in Cu(II) treatments. Additional UV exposure increased accumulation in both treatments, with the effect being stronger for Cu accumulation from CuO-NPs than for dissolved Cu(II). Photosynthetic capacity was strongly reduced by UV treatment, whereas remained unaffected by Cu(II) or CuO-NP treatments. Similarly, the increase of SOD activity was more pronounced in the UV treatments. On the other hand, POD activity enhancement was strongest in the plants exposed to CuO-NPs for 24 h. Expression of the copper transporter COPT1 as revealed by RT-qPCR was inhibited by Cu(II) and CuO-NP treatment, limiting the uptake of excess Cu into the cells. Overall, the combined exposure of E. nuttallii to UV radiation with CuO-NPs or Cu(II) has a higher impact than exposure to CuO-NPs or Cu(II) alone. The results imply that heavy pollution of natural water with CuO-NPs or dissolved Cu might have stronger effects in combination with natural UV irradiation on organisms in situ .